Considerations for prostate cancer - Garibaldi P., Alejandro (1956)
We compared the histology of two batches of prostates operated on the same service, with 10-year interval. having found some interesting information in relation to Prostate Cancer. Thus, in 1946, Dr. Eduardo Delgado Castro recorded in his thesis, 50 prostates operated on in the Department of Urology of the Hospital "Daniel A. Carrión" histologically studied by Prof. Peter Weiss, 18% were be adenocarcinomas, 30% were considered as atypical adenomas and the remaining 52% were classified as benign adenomas.